Determinants of performance in paced and maximal 800-m running time trials - Bellinger, P.; Derave, W.; Lievens, E.; Kennedy, B.; Arnold, B.; Rice, H.; Minahan, C. (Medicine & Science in Sports & Exercise, 2021)
Purpose : We aimed to identify the underpinning physiological and speed/mechanical determinants of different types of 800-m running time trials (i.e., with a positive or negative pacing strategy) and key components within each 800-m time trial (i.e., first and final 200 m). Methods: Twenty trained male 800-m runners (800-m personal best time (min:s): 1:55.10 ± 0:04.44) completed a maximal 800-m time trial (800MAX) and one pacing trial, whereby runners were paced for the first lap, and speed was reduced by 7.5% (800PACE) relative to 800MAX, whereas the last lap was completed in the fastest time possible. Anaerobic speed reserve, running economy, the velocity corresponding with V?O2peak (VV?O2peak), maximal sprint speed (MAXSS), maximal accumulated oxygen deficit, and sprint force-velocity-power profiles were derived from laboratory and field testing. Carnosine content was quantified by proton magnetic resonance spectroscopy in the gastrocnemius and soleus and expressed as a carnosine aggregate Z (CAZ) score to estimate muscle typology. Data were analyzed using multiple stepwise regression analysis. Results: MAXSS and vV.O2peak largely explained the variation in 800MAX time (r2 = 0.570; P = 0.020), whereas MAXSS was the best explanatory variable for the first 200-m time in 800MAX (adjusted r2 = 0.661, P < 0.001). Runners with a higher CAZ score (i.e., higher estimated percentage of type II fibers) reduced their last lap time to a greater extent in 800PACE relative to 800MAX (adjusted r2 = 0.413, P < 0.001), whereas better maintenance of mechanical effectiveness during sprinting, a higher CAZ score and vV.O2peak was associated with a faster final 200-m time during 800PACE (adjusted r2 = 0.761, P = 0.001). Conclusions: These findings highlight that diversity in the physiological and speed/mechanical characteristics of male middle-distance runners may be associated with their suitability for different 800-m racing strategies to have the best chance of winning.